2007
DOI: 10.1016/j.neuroscience.2006.12.061
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment selectively increases glutamatergic responses in layer II/III of the auditory cortex of the rat

Abstract: Prolonged exposure to environmental enrichment (EE) induces behavioral adaptation accompanied by detectable morphological and physiological changes. Auditory EE is associated with an increased auditory evoked potential (AEP) and increased auditory gating in the primary auditory cortex. We sought physiological correlates to such changes by comparing synaptic currents in control vs. EE-raised rats, in a primary auditory cortex (AI) slice preparation. Pharmacologically isolated glutamatergic or GABA(A)-receptor-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
4
26
0
1
Order By: Relevance
“…However, given that the amphetamine-induced increase in glutamate was blocked completely by MK-801 in EC rats, an involvement of NMDA receptors is implicated. Consistent with this, compared to IC rats, EC rats have increased glutamate transmission in cortex and hippocampus (Nichols et al, 2007;Segovia et al, 2006) and decreased expression of NMDA receptor subunits in NAcc (Wood et al, 2005). The decrease in NMDA receptor expression in NAcc may represent a compensatory down-regulation in response to an enhanced glutamate signal.…”
Section: Discussionsupporting
confidence: 58%
“…However, given that the amphetamine-induced increase in glutamate was blocked completely by MK-801 in EC rats, an involvement of NMDA receptors is implicated. Consistent with this, compared to IC rats, EC rats have increased glutamate transmission in cortex and hippocampus (Nichols et al, 2007;Segovia et al, 2006) and decreased expression of NMDA receptor subunits in NAcc (Wood et al, 2005). The decrease in NMDA receptor expression in NAcc may represent a compensatory down-regulation in response to an enhanced glutamate signal.…”
Section: Discussionsupporting
confidence: 58%
“…To avoid the possibility of any sex-based variability in cortical processing of sounds, we restricted our study to female rats. The enriched and standard housing conditions were identical to those in earlier reports published from our lab (Bose et al 2010;Engineer et al 2004;Kilgard et al 2007;Nichols et al 2007;Percaccio et al 2005). Rats in both environments received food and water ad libitum, were on a reverse 12:12-h light-dark cycle, and were exposed to the same constant temperature and humidity levels.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, PAF bandwidths narrow to a greater extent than can be explained by direct transmission of bandwidth changes in A1, suggesting increased local stimulus-evoked surround inhibition in PAF after enrichment. The fact that basal GABA levels decrease (Sale et al 2007) but there is no decrease in evoked GABA release in primary sensory cortex (Nichols et al 2007) suggests that enrichment could affect basal and evoked GABA levels differently in the cortex. We propose that while enrichment decreases basal levels of GABA, it increases local stimulus-evoked GABAergic inhibition of pyramidal cells in PAF.…”
Section: Mechanism Of Paf Reorganization: Brain Regions Involvedmentioning
confidence: 99%
“…Nichols et al (2007) have shown that exposure to EE induces an AMPA-receptor mediated increase in EPSC amplitudes in supragranular layers of the auditory cortex, with no changes in GABA-ergic transmission, while the increase in PPD after EE demonstrated by Percaccio et al (2005) suggests an increase in the transmitter release probability of excitatory synapses.…”
Section: Mechanisms Underlying Ee-induced Changes In Neuronal Functionmentioning
confidence: 99%